Neutrophil Signaling during Myocardial Infarction Wound Repair - Daseke, Michael J. (Cell Signal, 2020)
Neutrophils are key effector cells of the innate immune system, serving as a first line of defense in the response to injury and playing essential roles in the wound healing process. Following myocardial infarction (MI), neutrophils infiltrate into the infarct region to propagate inflammation and begin the initial phase of cardiac wound repair. Pro-inflammatory neutrophils release proteases to degrade extracellular matrix (ECM), a necessary step for the removal of necrotic myocytes as a prelude for scar formation. Neutrophils transition their phenotype over time to regulate MI inflammation resolution and stabilize scar formation. Neutrophils contribute to the evolution from inflammation to resolution and scar formation by serving anti-inflammatory and repair functions. As anti-inflammatory cells, neutrophils contribute ECM proteins during scar formation, in particular fibronectin, galectin-3, and vimentin. The diverse and polarizing functions that contribute to MI wound repair make this innate immune cell a viable target to improve MI outcomes. Thus, understanding the signaling involved in neutrophil physiology in the context of MI may help to identify novel therapeutic targets.